NU DAN DÄ€R AL-ISLÄ€M: SEBUAH KAJIAN TERHADAP KONSTELASI SYARIAT ISLAM DI INDONESIA - Abd.Rahman, Zayad; Syamsuri, Ali (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2020)
This study aims to uncover the concept of dÄr al-islÄm and the application of sharia in the context of the state according to Nahdhatul Ulama as one of the traditionalist views. The significance of this research lies in the ways and views of NU that differ from modernist understandings such as the Indonesian Islamic State (NII), even Masyumi in understanding dÄr al-islÄm. It cannot be denied, NU is a massive massive religious organization whose thoughts and movements greatly influence the religious dynamics in Indonesia and have an important role in the formalization of formalization of sharia in the body of the state. Methodologically, this research is a library research which is approached with a historical approach. One-way approach is needed because this research takes historical thinking. The data collected draws on the results of the 11th Congress of the NU Congress in Banjarmasin as primary data, while books and other documents become secondary data. The data collected is analyzed for validity through content analysis to create replicable inference. The conclusion of the study is the concept of dÄr al-islÄm according to NU does not make Islam as a formal Islamic state that requires the enactment of sharia. However, what is meant by the concept of dÄr al-islÄm is a religious term that means wilayat al-islamiyah (Islamic territory) which must be preserved and maintained as a unity as part of the Islamic tradition. So with this concept all Muslims are required to fight and expel invaders from the motherland. The concept of dÄr al-islÄm does not want the formalization of sharia or to make the state as an Islamic state as understood by radical schools.Keywords: NU, DÄr al-IslÄm, ShÄrÄ«ah